2006
DOI: 10.4049/jimmunol.176.12.7621
|View full text |Cite
|
Sign up to set email alerts
|

Class IA Phosphatidylinositide 3-Kinases, rather than p110γ, Regulate Formyl-Methionyl-Leucyl-Phenylalanine-Stimulated Chemotaxis and Superoxide Production in Differentiated Neutrophil-Like PLB-985 Cells

Abstract: Class I PI3Ks, through the formation of phosphatidylinositol-3,4,5-trisphosphate (PI(3,4,5)P3), are thought of as essential elements of the neutrophil response to chemotactic factors. Moreover, the recent development of PI3K-deficient mice and isoform-specific inhibitors enabled examinations of the contribution of the distinct PI3K isoforms in neutrophil activation. However, the results of these various studies are conflicting, and the exact role of the different PI3K isoforms is not yet clearly established, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 43 publications
3
36
2
Order By: Relevance
“…Prior studies in PI3K␥-deficient mice showed impaired fMLP-stimulated PMN respiratory burst activity (17,41) indicating the important role of GPCR-coupled PI3K␥ in the activation of NADPH oxidase. Using dominant negative protein inhibitors of class IA and IB PI3K, a recent study has demonstrated the dominant role of class IA PI3K in fMLPstimulated superoxide generation (36). In the present study, we addressed the role of class IA PI3K in mediating TNF-␣-induced activation of PMN NADPH oxidase and its consequences in the mechanism of lung inflammation and injury.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in PI3K␥-deficient mice showed impaired fMLP-stimulated PMN respiratory burst activity (17,41) indicating the important role of GPCR-coupled PI3K␥ in the activation of NADPH oxidase. Using dominant negative protein inhibitors of class IA and IB PI3K, a recent study has demonstrated the dominant role of class IA PI3K in fMLPstimulated superoxide generation (36). In the present study, we addressed the role of class IA PI3K in mediating TNF-␣-induced activation of PMN NADPH oxidase and its consequences in the mechanism of lung inflammation and injury.…”
Section: Discussionmentioning
confidence: 99%
“…One example of these conflicting data is neutrophil chemotaxis towards the bacterial peptide formyl-Met-Leu-Phe (fMLP). Some groups have proposed that PI3K activity is an absolute requirement for migration towards fMLP (Sadhu et al, 2003), whereas other groups have identified a partial requirement for PI3K in migration towards fMLP (Boulven et al, 2006;Ferguson et al, 2007), and still other groups have demonstrated that chemotaxis towards fMLP is independent of PI3K (Heit et al, 2002). In addition, recent studies using Dictyostelium have demonstrated that chemotaxis, at least under some circumstances, can occur in the absence of both PI3K and its negative regulator PTEN (Andrew and Insall, 2007;Loovers et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An undifferentiated myeloid cell line was used in most experiments, namely, the PLB 985 cell line [8], originally obtained from the German Collection of Microorganisms and Cell Cultures. These lines were cultured in RPMI 1640 medium containing 10% FBS, pyruvate and antibiotics at 37°C in a 5% CO 2 humidified atmosphere and chemical induction of differentiation was based on adding dimethylsulfoxide (DMSO, 1.3% v/v) for 5 to 7 days in the culture medium, a step known to upregulate the expression of the human FPR 1 in these cells [9].…”
Section: Cells and Stimulationmentioning
confidence: 99%
“…Differentiated PLB 985 cells support f-Met-Leu-Phe-induced the O 2 -release assay based on cytochrome c reduction that was applied as described [9].…”
Section: Superoxide Measurementmentioning
confidence: 99%